2011
DOI: 10.1590/s0100-40422011000300011
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da influência dos particulados no fenômeno de agregação dos asfaltenos por espectrometria de varredura óptica

Abstract: . The processing of national petroleums causes many operational problems due to the asphaltene aggregation phenomena. To evaluate the behavior of these phenomena, a study based on optical scan technique was carried out to understand the behavior of pure oils and their mixtures. The evaluation according to criteria established by ASTM D7061-06 1 gives a result of asphaltene flocculation of according to the separability number. In this study, the aspects related to the existence of colloidal forms of peptized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…4,9,14,18 The main limitations of the method to determine the precipitation onset of asphaltenes utilizing flocculant titration with monitoring of the absorption intensity by NIR are related to two factors: (i) in viscous oil samples, it is only possible to identify the effect of dilution of the sample, not the precipitation of asphaltenes; and (ii) the interference of the particles present in crude oil (from the reservoir rock formation) is not considered. 7,42 However, these drawbacks are not found when analyzing model systems, as those containing asphaltenes in toluene analyzed here.…”
Section: ■ Introductionmentioning
confidence: 98%
“…4,9,14,18 The main limitations of the method to determine the precipitation onset of asphaltenes utilizing flocculant titration with monitoring of the absorption intensity by NIR are related to two factors: (i) in viscous oil samples, it is only possible to identify the effect of dilution of the sample, not the precipitation of asphaltenes; and (ii) the interference of the particles present in crude oil (from the reservoir rock formation) is not considered. 7,42 However, these drawbacks are not found when analyzing model systems, as those containing asphaltenes in toluene analyzed here.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Wiehe and Kennedy, studying oil compatibility, have determined the critical solubility parameter at the onset of asphaltenes flocculation for Souedie Crude oil at around 16.35 MPa 1/2 . Even though this value can change for different crude oils and Nikooyek and Shaw study has concluded that the use of the solubility parameter is not suitable to describe asphaltenes + diluent mixture behavior, eq has been used to determine the solubility parameter of the crude oil, assuming δ M = 16.35 MPa 1/2 . , where δ i is the solubility parameter of component i and φ i is the fraction by volume of component i in the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] The deposition of asphaltenes is associated with the flocculation of particles, which starts due to variations in the composition of the crude oil and temperature, pressure and flow regime. [15][16][17] The flocculation can be promoted by the addition of apolar solvents to the oil (such as n-pentane and n-heptane). When a large quantity of aromatic solvent is present, molecular aggregates can be formed in the dispersed medium.…”
Section: Introductionmentioning
confidence: 99%